1996
DOI: 10.2307/1382821
|View full text |Cite
|
Sign up to set email alerts
|

Sexual Segregation in Ungulates: New Directions for Research

Abstract: We reviewed the literature on sexual segregation in polygynous ungulates in an effort to clarify terms and concepts, summarize recent information that supports or discredits three broadly defined hypotheses, and suggest directions for future research that should help resolve when and why the sexes segregate in these large mammals. The hypotheses discussed include those based on intersexual differences in energetics and security (reproductive-strategy hypothesis), body size dimorphism and dietary requirements (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
270
1
6

Year Published

2008
2008
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 337 publications
(285 citation statements)
references
References 44 publications
8
270
1
6
Order By: Relevance
“…The role of ecological mechanisms in sexbiased fecal larvae counts has not been sufficiently addressed, despite sexual segregation being well-documented in bighorn sheep and other ungulates (Main and Coblentz, 1990;Main et al, 1996;Bowyer, 2004). On Antelope Island, distribution of ram and nursery groups differed during the summer, with similar patterns in the Newfoundland Mountain population.…”
Section: Discussionmentioning
confidence: 99%
“…The role of ecological mechanisms in sexbiased fecal larvae counts has not been sufficiently addressed, despite sexual segregation being well-documented in bighorn sheep and other ungulates (Main and Coblentz, 1990;Main et al, 1996;Bowyer, 2004). On Antelope Island, distribution of ram and nursery groups differed during the summer, with similar patterns in the Newfoundland Mountain population.…”
Section: Discussionmentioning
confidence: 99%
“…A number of differences between the sexes in both species' composition of a diet and its quality have been reported in ungulate species. Main et al (1996) reported that in ungulates, sexes segregate because sexual differences and body size lead to different energy requirements and hence food selection. This variation between the male and female is also attributed to their body size.…”
Section: Effect Of Sex On Forage Preference By the Camelsmentioning
confidence: 99%
“…In addition, energy expenditure and transfer of nutrients through lactation increase selectivity in reproducing females for food sources rich in nitrogen, sodium or calcium (Clutton-Brock et al, 1986b;Iason et al, 1986). Sexually dimorphic males and females may, therefore, select different plant species or habitats with differing plant and nutrient availability and hence segregate in space (Main et al, 1996). Males and females often use different habitat types, but also overlap in habitat use (Villaret and Bon, 1995).…”
Section: Effect Of Sex On Forage Preference By the Camelsmentioning
confidence: 99%
“…Sex-specific differences in mother-infant interactions could conceivably give way to early life sex-specific social learning patterns of habitat preference. Such differences could be the underlying mechanism responsible for sexual segregation of habitat selection, a widespread phenomenon which occurs in mouflon (Guilhem et al, 2006) and bighorn sheep (Geist and Petocz, 1977) as well as ibex (Villaret and Bon, 1995), and other mammals (Main et al, 1996).…”
mentioning
confidence: 99%